2005
DOI: 10.1254/jphs.fp0040592
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Real-Time Detection of Initiator- and Effector-Caspase Activation by Double Fluorescence Resonance Energy Transfer Analysis

Abstract: Abstract. Fluorescence resonance energy transfer (FRET) with green fluorescent protein (GFP) variants has become widely used for biochemical research. In order to expand the choice of fluorescent range in FRET analysis, we designed various color versions of the FRET-based probes for caspase activity, in which the substrate sequence of the caspase was sandwiched by donor and acceptor fluorescent proteins, and studied the potential of these color versions as fluorescent indicators. Six color versions were constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 15 publications
(13 reference statements)
1
33
1
Order By: Relevance
“…Such a probe has been used to determine the kinetics of caspase activation at the single cell level as a rapid process reaching completion in a matter of minutes (18). It has also been demonstrated that, through the use of two different FRET pairs, it is possible to measure simultaneously caspase-mediated cleavage of two different substrates (19,20). However due to a considerable overlap in the substrate specificities of each caspase it is difficult to interpret from such experiments which specific caspases have been activated.…”
Section: Caspase Activationmentioning
confidence: 99%
“…Such a probe has been used to determine the kinetics of caspase activation at the single cell level as a rapid process reaching completion in a matter of minutes (18). It has also been demonstrated that, through the use of two different FRET pairs, it is possible to measure simultaneously caspase-mediated cleavage of two different substrates (19,20). However due to a considerable overlap in the substrate specificities of each caspase it is difficult to interpret from such experiments which specific caspases have been activated.…”
Section: Caspase Activationmentioning
confidence: 99%
“…This dual-caspase fluorescent substrate has several desirable properties as a biological sensor for caspase-3 and caspase-6 activities in living cells. Both caspase-3 and caspase-6 are classified as effector caspases that makes it difficult to separate their precise position within the apoptotic cascade by monitoring only cellular activities in living cells by single caspase substrates or simultaneously loading cells with separated caspase substrates (8,25,27). We circumvented this difficulty by designing a fluorescent substrate that separately inserted a caspase-3 recognition motif (DEVD) and a caspase-6 cleavage site (VEID) within the same molecule.…”
Section: Measurement Of Two Caspase Activities By a Single Fluorescenmentioning
confidence: 99%
“…Chemical substrates, including fluorogenic substrates and fluorochrome-labeled inhibitors of caspases (FLICAs), have been developed for this purpose (8,(21)(22)(23). More recently, genetically engineered probes have been described, consisting of a CFP-YFP fusion protein in which the fluorophores are separated by a very short FRET-permissive linker containing at least one caspase cleavage site, such as DEVD, LEVD, or another caspase-sensitive cleavage sequence (24)(25)(26)(27)(28)(29)(30)(31)(32)(33). The linker is cleaved by activated caspases, triggering decreased FRET because of the resultant physical separation of CFP and YFP molecules.…”
mentioning
confidence: 99%
“…Further, these probes will be suitable for coimaging because CFP and YFP have sufficiently distinct excitation properties and there will be minimal contamination of the two FRET channels. For example, FRET-based biosensors for caspase activities using these FRET pairs have been constructed and imaged simultaneously in cells with minimal signal contamination (40). This serves as a proof of principle that a CR and a YR FRET-based biosensor can be used for coimaging of two distinct signaling events in the same cell.…”
Section: Coimaging Fret-based Biosensors Via Spectrally Distinct Fluomentioning
confidence: 99%
“…There are a number of ways around this problem such as: coimaging a FRET biosensor with a spectrally distinct single-fluorophore biosensor (16) (Fig. 2B), coimaging two FRET pairs that use distinct donors and a common acceptor (40) (Fig. 2C), and utilizing FPs that have unique excitation and emission properties that make them suitable as FRET partners yet distinguishable from the other FPs in a filter-based setup (38,39) (Fig.…”
Section: Coimaging Fret-based Biosensors Via Spectrally Distinct Fluomentioning
confidence: 99%